Inventory management and performance of manufacturing firms. (21st July 2021) - Panigrahi, Rashmi Ranjan; Jena, Duryodhan; Tandon, Deepak; Meher, Jamini Ranjan; Mishra, Padma Charan; Sahoo, Ansuman
Inventory management practices (IMP) are prevalent in managing and controlling inventory in an organisation. The study aims to measure the performance of steel manufacturing firms by determining the effect of distribution turnover and inventory automation over competitive strength and operational efficiencies. From the extant literature, it is evident that the above relationship is very limited in the Indian context. Data were collected from five selected manufacturing firms from the state of Odisha, India. Respondents of the study are some key officials, viz. operations manager, production manager, purchase manager and warehouse manager from various manufacturing firms. As per the need of the study, various statistical tools such as correlation, multiple regression, confirmatory factor analysis and Kolmogorov-Smirnov test were used. The outcome of the study concludes that IMP has significant impact on firm performance and also contributes to the existing body of knowledge by helping inventory management practitioners of manufacturing industry.